2014
DOI: 10.1017/s0954394514000052
|View full text |Cite
|
Sign up to set email alerts
|

A Cognitive Construction Grammar approach to the pluralization of presentational haber in Puerto Rican Spanish

Abstract: In this paper, I present an analysis of the pluralization of haber ‘there is/are’ in Puerto Rican Spanish (e.g., habían fiestas ‘there were parties’) as an ongoing language change from below in which the impersonal argument-structure construction (<AdvPhaberObj>) is being replaced by a personal variant (<AdvPhaberSubj>). Speakers pluralize presentational haber in about 41% of the cases, and linguistic conditioning factors are ‘typical action chain-position of the noun's referent,’ polarity of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
1
11
0
2
Order By: Relevance
“…For age, this result was already anticipated in the discussion of the hypotheses, because earlier investigations (Claes 2014;D'Aquino-Ruiz 2008;Fontanella de Weinberg 1992b: 44) have shown the pluralization of haber to be a slowly advancing process, which may be invisible in apparent time. By the same token, hypothesis 7 already anticipates that the alternations between the two constructions may not display any style shifting.…”
Section: Principles Of Linguistic Changementioning
confidence: 59%
See 4 more Smart Citations
“…For age, this result was already anticipated in the discussion of the hypotheses, because earlier investigations (Claes 2014;D'Aquino-Ruiz 2008;Fontanella de Weinberg 1992b: 44) have shown the pluralization of haber to be a slowly advancing process, which may be invisible in apparent time. By the same token, hypothesis 7 already anticipates that the alternations between the two constructions may not display any style shifting.…”
Section: Principles Of Linguistic Changementioning
confidence: 59%
“…'But on a, on a whole, eh, there are SG characteristics that one has to recognize that they are worth it, which this particular sector has.' However, in my study of haber pluralization in Puerto Rican Spanish (Claes 2014), I have shown that all of these results can be subsumed under the term 'typical action-chain position'. Indeed, In contrast, Table 3 shows that nouns that refer to more typical endpoints of the action chain (i.e., typical patients, exemplified in 17-18) or to typical settings of events (e.g., aeropuertos 'airports' in example 19) are more common with singular haber, as is shown by the negative log odds values.…”
Section: Markedness Of Codingmentioning
confidence: 95%
See 3 more Smart Citations